2004
DOI: 10.1002/lt.20319
|View full text |Cite
|
Sign up to set email alerts
|

De Novo neoplasia after liver transplantation: An analysis of risk factors and influence on survival

Abstract: Immunosuppression increases the risk of posttransplant malignancy and it may increase posttransplant mortality. The finding of factors related to the development of posttransplant malignancy may serve as a guide to avoid those risk factors and to develop strategies of posttransplant surveillance. The incidence and risk factors of malignancy were studied in 187 consecutive liver transplant recipients surviving more than 3 months. None of the 12 patients surviving less than 3 months had de novo neoplasia. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
125
3
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 22 publications
18
125
3
8
Order By: Relevance
“…Differences in latitude and sun exposure and immunosuppressive protocols may explain these differences. We found no mortality in these patients, thus confirming the low mortality observed by other authors [9,17,23,24]. In our outpatient clinic, dermatological evaluations are made in all patients so that these lesions can be diagnosed and treated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Differences in latitude and sun exposure and immunosuppressive protocols may explain these differences. We found no mortality in these patients, thus confirming the low mortality observed by other authors [9,17,23,24]. In our outpatient clinic, dermatological evaluations are made in all patients so that these lesions can be diagnosed and treated.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, when survival was compared between patients with skin and non-skin tumors, differences were evident. It has been well described that patients who develop DN have shorter survival post-LT [23] and that the DN represents a major cause of late mortality following DN, as recently published by our group [6]. Although a case-control analysis to assess this fact was not made in the present study, shorter survival after DN was observed in patients developing non-skin tumors.…”
Section: Discussionmentioning
confidence: 61%
“…12 Currently, long-term graft loss and death are not commonly related to rejection but are often due to age-related complications, such as cardiovascular disease and de novo cancers. 13,14 The rate of de novo cancers after LTx has been reported to range from 3% to 26%, [15][16][17][18] and the variation is partly due to the length of follow-up, different ways of reporting, and geographic variations in de novo malignancies. Although registry data of de novo cancers provide a valuable source for accounting for the various types of malignancies; these registries do not include the denominator of the population at risk.…”
Section: See Article On Page 1428mentioning
confidence: 99%
“…Herrero et al 16 reviewed 187 cases and found 63 malignancies (lymphoid lesions included). On a univariate analysis, for they found age to be a significant risk factor for de novo cancers (P ϭ 0.01).…”
Section: Rate Of De Novo Malignancies In Relation To the Recipient's Agementioning
confidence: 99%
“…The incidence of malignancies in the post-SOT setting could not be estimated from our study as our patients were identified from a pool of cancer patients rather than transplant patients. Many reports have estimated the incidence to range between 2.6% and 26% [8,9] . Cancer can develop as early as 22 months into post-SOT but may also take up to 10 years to be detected [7] .…”
Section: Discussionmentioning
confidence: 99%